Radar data analysis and rain modelling software - Yeo, Shawn Qing Wen. (2009)
In satellite and terrestrial telecommunication links, it has been known that rainfall causes attenuation to these communication links which causes signal levels to be degraded thus affecting the link performance. Therefore, to ensure reliability of communication in a tropical climate like Singapore, the study of the effect of rainfall on communication systems is extremely important.